2020
DOI: 10.2147/dmso.s259770
|View full text |Cite
|
Sign up to set email alerts
|

<p>Screening for Metabolic Syndrome Using an Integrated Continuous Index Consisting of Waist Circumference and Triglyceride: A Preliminary Cross-sectional Study</p>

Abstract: Background: It has been suggested that hypertriglyceridemic waist (HW) phenotype is strongly associated with metabolic syndrome (MetS); however, there are very limited studies integrating triglyceride (TG) and waist circumference (WC) into a continuous variable to investigate the predictive power of this phenotype. Inspired from the triglyceride glucose index (TyG), we developed an integrated continuous index termed waist-triglyceride index (WTI) which was calculated as Ln [TG (mg/dl) WC (cm)/2]. Objective: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
1
16
1
Order By: Relevance
“…Inspired by the TyG, WTI was first proposed by Liu et al. ( 20 ). Their study showed that WTI and MetS risk in the Chinese population was associated, the AUC of WTI predicting MetS is 0.881 in women and 0.830 in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the TyG, WTI was first proposed by Liu et al. ( 20 ). Their study showed that WTI and MetS risk in the Chinese population was associated, the AUC of WTI predicting MetS is 0.881 in women and 0.830 in men.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, inspired by the formula of the TyG index, Liu et al. combined WC with TG to develop a new index called waist-triglyceride index (WTI), which showed a strong ability to distinguish MetS ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of the hypertriglyceridemic waist phenotype was first proposed by Lemieux et al based on the evidence that high TG or WC alone were inadequate to identify the metabolic triad 9 . This phenotype has been widely accepted in risk assessment or prediction of high visceral fat 25 , diabetes 26 , hypertension 27 , metabolic syndrome 28 , atherosclerosis 29 , cardiovascular diseases 30 , and renal dysfunction 31 . All these results support that the hypertriglyceridemic waist phenotype is a cost-effective screening tool that can be used in clinical practice and is an efficient and effective phenotype that can be used for health management.…”
Section: Discussionmentioning
confidence: 99%
“…The HTGW phenotype has also been widely accepted in risk assessment or prediction of high visceral fat, 14 metabolic syndrome, 54 and fatty liver. 55 All these results support that the HTGW phenotype is a cost-effective screening tool that can be used in clinical practice and an efficient and effective phenotype that can be used in health management.…”
Section: Discussionmentioning
confidence: 99%